Global Dynamics of a Diffusive Leslie-Gower Predator-Prey Model with Fear Effect (Journal of Nonlinear Modeling and Analysis, 2024)
A diffusive Leslie-Gower predator-prey model with fear effect isconsidered in this paper. For the kinetic system, we show that the uniquepositive equilibrium is globally asymptotically stable. Moreover, we find thathigh levels of fear could decrease the population densities of both prey andpredator in a long time. For the diffusive model, we obtain the similar resultsunder certain conditions.